A case study of the strategic leadership displayed by Kevin Hedderwick at Famous Brands between 2004-2009 - Tom, Lubabalo Alexander (Rhodes University, Faculty of Commerce, Investec Business School, 2011)
Research studies and the review of academic literature has found that strategic leadership had a direct impact on organisational climate, and that climate in turn accounted for nearly one third of the financial results of organisations (Goleman, 2000). The conclusion from research conducted across 13 industries established that over a 20 year period, leadership accounted for more variations in performance than any other variable (Northouse, 2006). This thesis confines its research to a case study on Famous Brands. Famous Brands is currently one of Africa's leading Quick Service Restaurant and Casual Dining franchisors and is also represented in the United Kingdom. The Group also has a manufacturing arm and supplies its franchisees, the retail trade and the broader hospitality industry with a wide range of meat, sauce, bakery, ice cream, fruit juice and mineral water products. At the time when the company's name changed from Steers Holdings to Famous Brand in 2004, Kevin Hedderwick was appointed as Chief Operating Officer. The research examines how Kevin Hedderwick has exercised strategic leadership and thereby influenced Famous Brands' performance. Hedderwick displays qualities, attributes and behaviours that are characterized by the phenomenon of "strategic leadership" . A quantitative analysis of Famous Brands financial performance (between 2005 and 2009) was undertaken. Further qualitative descriptions were used to further give meaning to the financial results. The success experienced by Famous Brands since Hedderwick's appointment, seem to suggest that strategic choices and initiatives have been met with great success. The research is presented in the form of a case study that can be developed into a teaching case to be used in the classroom to illustrate the exercise of strategic leadership. The researcher explored a qualitative research framework by collecting and assimilating data from available documentation, and from a formal interview that was conducted with Mr Hedderwick. Information was also obtained from interviews that were conducted with other senior executives and influential personnel. This research concludes that the success of organisations is dependent on the interventions of a strategic leader who displays a specialist set of skills and behaviours. These strategic leaders have the ability to successfully influence their employees, thereby creating an enabling environment for the implementation of their strategic choices.
Keywords: Hedderwick, Kevin; Famous Brands; Leadership -- South Africa -- Case studies; Strategic planning -- South Africa -- Case studies; Corporate culture -- South Africa -- Case studies; Organizational behavior -- South Africa -- Case studies; Financial management -- South Africa -- Case studies; Food industry and trade -- South Africa -- Case studies